KEPENTINGAN KERJASAMA OTORITAS JASA KEUANGAN (OJK) DENGAN BANK OF THAILAND (BOT) DALAM PENGAWASAN PERBANKAN 2018-2024 - Santoso, Sagit Hartono; Witus, Petraniwati (Moestopo Journal of International Relations (MJIR), 2024)
The purpose of this study is to analyze how the Financial Services Authority and Bank of Thailand Cooperate in Banking Supervision. The method used in this study is qualitative with document analysis from various sources, including books, journals, and official websites such as ojk.go.id and kemlu.go.id. In this study, the theories used include international cooperation, national economic interests, and Banking. The study shows that this cooperation aims to strengthen the foundation of banking supervision in both countries based on the Basel Core Principles for Effective Banking Supervision.